ANALYSIS OF THE INFLUENCE OF SOCIAL MEDIA ADDICTION ON DEPRESSION IN ADOLESCENTS AT SURABAYA HIGH SCHOOL - Athilla, Qania; Rusyid , Ghozali (PT ANTIS INTERNATIONAL PUBLISHER, 2025)
Objective: This study aimed to examine the impact of social media addiction on depression levels among adolescents at Maryam High School in Surabaya, motivated by growing concerns over the mental health consequences of excessive digital engagement. Method: Employing a quantitative correlational design, the study involved 100 students selected through saturated sampling. Data were gathered using the Social Media Addiction Scale Student Form (SMAS-SF) and the Beck Depression Inventory-II (BDI-II), and analyzed via simple linear regression using JASP software. Results: The analysis revealed a significant positive relationship between social media addiction and depression (r = 0.615, p < 0.001), with a determination coefficient (R²) of 0.360, indicating that 36% of the variance in depression levels could be attributed to social media addiction. The regression model (Y = -19.832 + 0.406X) further demonstrated that higher addiction scores predicted increased depressive symptoms. Novelty: This study contributes to the growing body of evidence linking social media use and adolescent mental health by providing specific data from an urban Indonesian context, thereby informing targeted school-based interventions to address digital well-being and emotional resilience in adolescents.